Biochemical and Transcriptomic Analysis Reveals Low Temperature-Driven Oxidative Stress in Pupal Apis mellifera Neural System - Xiangjie Zhu; Mingjie Cao; Chenyang Li; Chenyu Zhu; Han Li; Yuanmingyue Tian; Jiaqi Shang; Jiaqi Sun; Bingfeng Zhou; Xianda Wu; Shujing Zhou; Xinjian Xu (Insects)
Exposure to low temperatures during honeybee development has been shown to impede brain development and affect cognitive function in adult bees. On the other hand, neuronal damage due to oxidative stress has been reported in many cases. Hence, biochemical parameters related to oxidative stress in honeybee pupae brain were determined. The levels of GSH in the pupal brain decreased after 24 h and 48 h of exposure to low temperatures; there were also reduced activities of SOD and CAT enzymes following 48 h of low-temperature treatment compared to the control group. Furthermore, analysis of transcriptome data post-24 h and -48 h low-temperature stress revealed the suppression of the glutathione metabolism and peroxisome pathways in pupal brains. Additionally, expression pattern clustering analysis and KEGG enrichment showed that 10 differentially expressed genes with down-regulated expression trends post-low-temperature treatment were significantly enriched in the peroxisome pathway, including PEX10, highlighting their connection to peroxisome function. RT-qPCR validation was conducted on 11 core enriched genes in pathways identified via GSEA, and all these genes exhibited a downregulated expression pattern, confirming the inhibition of glutathione metabolism and peroxisome function under low-temperature stress. The present study showed that exposing honeybee pupae to low temperatures suppressed both the glutathione metabolism and peroxisome pathways, resulting in increased oxidative stress. This research enhances our understanding of how the pupal brain reacts to cold stress and illuminates the neural damage associated with low temperatures during honeybee capped brood development.